2017
DOI: 10.1080/00038628.2017.1336983
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with indoor environmental quality in BREEAM and non-BREEAM certified office buildings

Abstract: The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 26 publications
5
28
1
1
Order By: Relevance
“…They concluded there was not a significant difference in the assessments of occupant satisfaction with IEQ in buildings with and without LEED certification. The same conclusion was also reported in their subsequent study conducted by Altomonte et al in the UK based on the BREEAM (Building Research Establishment Environmental Assessment Method) certification. No significant difference was also reported by Menadue et al with respect to measured and subjectively rated thermal environment when four green and four conventional buildings were compared in Australia.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…They concluded there was not a significant difference in the assessments of occupant satisfaction with IEQ in buildings with and without LEED certification. The same conclusion was also reported in their subsequent study conducted by Altomonte et al in the UK based on the BREEAM (Building Research Establishment Environmental Assessment Method) certification. No significant difference was also reported by Menadue et al with respect to measured and subjectively rated thermal environment when four green and four conventional buildings were compared in Australia.…”
Section: Introductionsupporting
confidence: 83%
“…This is similar to that reported by Liang et al in Taiwan that occupants in green buildings expressed statistically higher satisfaction with overall IEQ. On the other hand, Altomonte and Schiavon and Altomonte et al reported differently that green buildings had equal or even less satisfaction with the building overall and with the workspace than conventional counterparts.…”
Section: Discussionmentioning
confidence: 96%
“…The expectations in a green building are more elevated as there are energy and water saving requirements, improved indoor environmental quality and compliance for environmentally conscious material selection and waste reduction. However, several authors pointed out green buildings did not meet the energy and water savings performances in the operational phases [5][6][7][8], nor on indoor environmental quality in actually promoting the building end-users' well-being [9,10]. Furthermore, the green building rating systems had a slight impact on tackling construction waste management as a result of weak appraisal measures [11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the additional cost of maintaining high IEQ levels in workplaces will be paid back in a reasonable period and generates additional monetary returns thereafter. It should be noted that buildings being rated as "sustainable and green" do not truly guaranty their compliance with the desired IEQ level [2][3][4][5]. Therefore, IEQ should be given specific focus while designing new buildings as well as in building retrofit plans.…”
Section: Overviewmentioning
confidence: 99%
“…They found that the building was performing low with regard to thermal comfort, ventilation, and ability to control indoor the environment. Altomonte et al [3] studied the occupant satisfaction on IEQ in LEED-and BREEAM-certified office buildings and highlighted the importance of incorporating IEQ in the criteria for sustainable and green building certifications.…”
Section: Ieq Of Sustainable and Green Buildingsmentioning
confidence: 99%